Analisis Determinasi Kinerja Anggaran dengan Konsep Value for Money pada Badan Pengelolaan Pendapatan Daerah (Bappenda) Kabupaten Tegal - Fera Tri Wulandari Hermanto; Andri Widianto; Aryanto Aryanto (Politeknik Ganesha Medan, 2021)
This research aimed to determine the influence of Accountability, Transparency, Control, towards Budgeting Performance of Value for Money Concept at Regional Revenue Management Agency (Bappenda) In Tegal. This research type was causal associative, Population of this research was all employees of Regional Revenue Management Agency (Bappenda) in Tegal. Methode of data collection used questionnaire. The analysis technique used multiple regression analysis.The results showed that Accountability towards Budgeting Performance of Value for Money Concept at Regional Revenue Management Agency (Bappenda)in Tegal, Transparency influence towards Budgeting Performance of Value for Money Concept at Regional Revenue Management Agency (Bappenda)in Tegal, Control influence towards Budgeting Performance of Value for Money Concept at Regional Revenue Management Agency (Bappenda)in Tegal